The Effectiveness of Instructional Leadership of School Principals - Nurabadi, Ahmad; Suhariadi, Fendy; Prestiadi, Dedi; Hung, Min-Ling (Angstrom Centre of Education, 2025)
This study aims at exploring instructional leadership of elementary school principals in Malang. It employs quantitative approach with descriptive study design aiming at describing phenomena as what they really are at times of study. It means that this study result in systematic, factual and accurate findings describing genuine condition. The objective of using descriptive study design is to describe or elaborate instructional leadership of elementary school principals in Malang. The subjects of study are 80 principals. The findings show that 62 respondents or 77,5% of school principals in Malang are on highly qualified category, 16 respondents or 20% are on qualified category and 2 respondents or 2,5% are on fairly qualified category. None is on less qualified category. Therefore, instructional leadership of elementary school principals in Malang are on quite high level or quite good category.